Konsep Landasan Dasar Pendidikan Karakter di Indonesia - Arif Rohman Hakim (Departement of Mathematics Education, 2023)
Education involves the transfer of knowledge from the previous generation to the next generation, the basic character of students is developed based on critical thinking skills, creativity, and social skills. The discrepancy between the implementation of education in Indonesia on the aspect of character decline. The purpose of this research is to increase students' understanding in developing their potential and skills according to the needs of the school. Research methodology with a qualitative approach - literature study. The results of the study describe that the basic concept pattern of the education system in Indonesia refers to curriculum development. There was a change in the curriculum from KTSP, K13 to the independent learning curriculum. teachers and students are worried about the change that happened today. The continuity of the curriculum in educational units makes it necessary for students and teachers to transform themselves to the actual situation. The mental strength of students and teachers in adapting is now a challenge for changing learning methods with innovation and creativity as well as planting character education through positive attitudes of teachers and students.